Strategies for mitigating communication anxiety among communication science students during seminar thesis examinations - Basri, Hasan; Nanda, Deri Sis; Susanto, Susanto (Iberoamerican Journal of Science Measurement and Communication, 2024)
Objective. The objective of this study was to examine the strategies employed by students to mitigate communication anxiety during thesis seminar examinations, a high-stress situation commonly encountered by students in communication science programs in Indonesia. Methodology. A qualitative study was conducted involving in-depth interviews with 130 communication science students from two universities in Lampung Province, Indonesia, who were about to undertake thesis seminar examinations. To ensure the integrity and reliability of the findings, triangulation analysis was applied. Results. The analysis revealed a number of strategies that students employ to mitigate anxiety during thesis seminar examinations. These strategies encompassed a range of techniques, including self-soothing practices, controlled breathing, reciting prayers, formulating preparatory notes, simulated presentations (mirror rehearsals), simulated interactions with peers, cognitive restructuring, and experiential learning. Conclusion. This study illuminated the array of strategies that students employ to mitigate anxiety during thesis seminar examinations, offering insights into coping methods well-suited to high-stress academic settings. The findings underscored the importance of integrating cognitive, emotional, and culturally relevant approaches into interventions designed to help students manage anxiety in public speaking contexts. Future research could further explore the effectiveness of these strategies across different academic and cultural settings, informing support programs that enhance students’ resilience and performance.